Internet, big data e discurso de ódio: reflexões sobre as dinâmicas de interação no Twitter e os novos ambientes de debate político - Cappi, Juliano (2017)
The present research analyzes the relations between, on the one hand, the interaction dynamics that have consolidated in the social networks and, on the other, the of hate speech online increase within these environments. The objectives of the research are, firstly, to investigate the unfolding of the increasingly widespread use of social network environments in political debates through the lens of cultural diversity, and to investigate possible patterns of dissemination of hate speech in the new debate sphere that emerges in these environments. The violence manifest in social networks has presented contours of racial prejudice, misogyny, homophobia and totalitarianism, often surpassing the limits of cyberspace. The analysis of the debates that took place on Twitter through the posts around the conviction of former President Luis Inacio Lula da Silva showed that the phenomenon of the filter bubbles was identified and followed the patterns already identified in international research. The analysis of the postings suggests that the construction of mutual identifications between groups of users ends up authorizing the systematic discourse of disrespect for dignity from characteristics that identify Lula as a whore, as a drunkard, a hobo and a thief. The theoretical framework uses the notion of communicational environment proposed by Baitello to support the assumption that the construction of identity and therefore the notion of alterity is increasingly related to the environment developed by the Internet applications present in our daily life. If the environment is a construction associated with subjectivity, an atmosphere generated by the availability of subjects - people and things - by their intentionality of establishing bonds, then the environments of interaction of cyberspace contribute to the structuring of the bonds so important for the construction of identity. We also used in the research the concept of filter bubbles in the terms of the work of Eli Pariser. The author proposes that the new digital Internet browsing environments are bubbles of familiarity, structured by systems of collection, analysis, classification and distribution of information using algorithms, in which users are inserted. Pariser disputes the widely accepted belief that the Internet environment is conducive to the contact with the diversity of expressions. The research was able to extend this approach by proposing that the bubbles are often manifested by ideological approximation. Finally, Eugenio Trivinho’s concept of cybercultural dromocracy is based on the violent condition in which recognition of alterity in modern society takes place. The methodological framework that guided the research is centered in the social networks analysis (SNA), based on the works of Raquel Recuero